Unexpected Presence of Graminan- and Levan-Type Fructans in the Evergreen Frost-Hardy Eudicot Pachysandra terminalis (Buxaceae): Purification, Cloning, and Functional Analysis of a 6-SST/6-SFT Enzyme(1)([W]) - Van den Ende, Wim (American Society of Plant Biologists, 2011)
About 15% of flowering plants accumulate fructans. Inulin-type fructans with β(2,1) fructosyl linkages typically accumulate in the core eudicot families (e.g. Asteraceae), while levan-type fructans with β(2,6) linkages and branched, graminan-type fructans with mixed linkages predominate in monocot families. Here, we describe the unexpected finding that graminan- and levan-type fructans, as typically occurring in wheat (Triticum aestivum) and barley (Hordeum vulgare), also accumulate in Pachysandra terminalis, an evergreen, frost-hardy basal eudicot species. Part of the complex graminan- and levan-type fructans as accumulating in vivo can be produced in vitro by a sucrose:fructan 6-fructosyltransferase (6-SFT) enzyme with inherent sucrose:sucrose 1-fructosyltransferase (1-SST) and fructan 6-exohydrolase side activities. This enzyme produces a series of cereal-like graminan- and levan-type fructans from sucrose as a single substrate. The 6-SST/6-SFT enzyme was fully purified by classic column chromatography. In-gel trypsin digestion led to reverse transcription-polymerase chain reaction-based cDNA cloning. The functionality of the 6-SST/6-SFT cDNA was demonstrated after heterologous expression in Pichia pastoris. Both the recombinant and native enzymes showed rather similar substrate specificity characteristics, including peculiar temperature-dependent inherent 1-SST and fructan 6-exohydrolase side activities. The finding that cereal-type fructans accumulate in a basal eudicot species further confirms the polyphyletic origin of fructan biosynthesis in nature. Our data suggest that the fructan syndrome in P. terminalis can be considered as a recent evolutionary event. Putative connections between abiotic stress and fructans are discussed.